“Time is My Own Treasure”: Parental Autonomy Support and Academic Procrastination Among Chinese Adolescents - Zhao W; Wang X; Li J; Li Q; Chen C (Psychology Research and Behavior Management, 2022)
Weiguo Zhao,1 Xinning Wang,1 Jiazheng Li,1 Qingtian Li,1 Chen Chen2 1School of Psychology, Shandong Normal University, Jinan, People’s Republic of China; 2Linyi Suhe Experimental School, Linyi, People’s Republic of ChinaCorrespondence: Weiguo Zhao, School of Psychology, Shandong Normal University, No. 1, Daxue Road, Changqing District, Jinan, 250358, People’s Republic of China, Tel +86 18765411698, Email wgzhao512sys@163.comPurpose: Previous studies have shown that academic procrastination not only affects middle school students’ academic performance but also causes them physical and psychological stress, as well as negative emotions. Therefore, it is necessary to explore the influencing factors of academic procrastination and its internal mechanisms. This study aims to explore the relationship between perceived parental autonomy support and academic procrastination, as well as the role of autonomous motivation and time management disposition.Participants and Methods: Cross-sectional data from 662 middle school students were collected using the Parental Autonomy Support Scale, Academic Procrastination Inventory for Middle School Students, Academic Self-Regulation Questionnaire and Adolescence Time Management Disposition Scale. SPSS and its PROCESS macro were used for data analysis.Results: After gender and age were controlled, the results showed that perceived parental autonomy support could not only directly predict middle school students’ academic procrastination but also predict three paths of procrastination: (1) the mediating role of autonomous motivation, (2) the mediating role of time management disposition, and (3) the chain mediating role of autonomous motivation and time management disposition.Conclusion: Autonomous motivation and time management disposition played a chain mediating role in the relationship between perceived parental autonomy support and academic procrastination in middle school students.Keywords: middle school students, academic procrastination, perceived parental autonomy support, autonomous motivation, time management disposition